PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS DAN DAYA JUANG SISWA - Nurhalizah, Siti; Siregar, Machrani Adi Putri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The quality of a nation's education and the current education system can be used to measure the nation's progress. The quality of education in Indonesia is currently very concerning. Upon observation, researchers stated that students lack the fighting spirit needed to overcome various challenges. Fighting power plays an important role in this. This study used qualitative research methods. The sample of this study consisted of all students of class X Accounting of SMKN 1 Sei Bejangkar. Pre-Experiment Design with One-Group Pretest-Posttest Design model was used in this study. Based on the research findings and discussion of the impact of guided discovery learning model on mathematical reasoning ability and students' fighting power on the material of function relation in class X Accounting of SMKN 1 Sei Bejangkar, it can be concluded that there is a good influence in the use of guided discovey learning model on mathematical reasoning ability and students' fighting power.